Porphyromonas pasteri and Prevotella nanceiensis in the sputum microbiota are associated with increased decline in lung function in individuals with cystic fibrosis. Issue 2 (3rd February 2022) - Webb, Karmel; Zain, Nur Masirah M.; Stewart, Iain; Fogarty, Andrew; Nash, Edward F.; Whitehouse, Joanna L.; Smyth, Alan R.; Lilley, Andrew K.; Knox, Alan; Williams, Paul; Cámara, Miguel; Bruce, Kenneth; et al.
Abstract : Although anaerobic bacteria exist in abundance in cystic fibrosis (CF) airways, their role in disease progression is poorly understood. We hypothesized that the presence and relative abundance of the most prevalent, live, anaerobic bacteria in sputum of adults with CF were associated with adverse clinical outcomes. This is the first study to prospectively investigate viable anaerobic bacteria present in the sputum microbiota and their relationship with long-term outcomes in adults with CF. We performed 16S rRNA analysis using a viability quantitative PCR technique on sputum samples obtained from a prospective cohort of 70 adults with CF and collected clinical data over an 8 year follow-up period. We examined the associations of the ten most abundant obligate anaerobic bacteria present in the sputum with annual rate of FEV1 change. The presence of Porphyromonas pasteri and Prevotella nanceiensis were associated with a greater annual rate of FEV1 change; −52.3 ml yr −1 (95 % CI-87.7;−16.9), –67.9 ml yr −1 (95 % CI-115.6;−20.1), respectively. Similarly, the relative abundance of these live organisms were associated with a greater annual rate of FEV1 decline of −3.7 ml yr −1 (95 % CI: −6.1 to −1.3, P =0.003) and −5.3 ml yr −1 (95 % CI: −8.7 to −1.9, P =0.002) for each log2 increment of abundance, respectively. The presence and relative abundance of certain anaerobes in the sputum of adults with CF are associated with a greater rate of long-term lung function decline. The pathogenicity of anaerobic bacteria in the CF airways should be confirmed with further longitudinal prospective studies with a larger cohort of participants.